Turkey : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Turkey. (IMF Staff Country Reports; Country Report ;, 2018)
Growth rebounded sharply in 2017, helped by strong policy stimulus in the wake of the 2016 post-coup attempt slump and by favorable external conditions. Although expansionary policies were initially warranted, they are no longer appropriate as the economy is showing clear signs of overheating. Monetary policy appears too loose and its credibility is low; and on- and off-budget fiscal policies (including credit guarantee schemes and PPP activities) are expansionary and risk undermining Turkey's hard-earned fiscal credibility. As a result, the economy faces internal and external imbalances: a positive output gap, inflation well above target, and a current account deficit of more than 5 percent of GDP. Meanwhile, political uncertainty and regional instability remain elevated, and the integration of the many refugees poses challenges.